Hura crepitans L. Extract: Phytochemical Characterization, Antioxidant Activity, and Nanoformulation - Antonio Vassallo; Maria Francesca Armentano; Rocchina Miglionico; Carla Caddeo; Claudia Chirollo; Maria Josefina Gualtieri; Angela Ostuni; Faustino Bisaccia; Immacolata Faraone; Luigi Milella (Pharmaceutics, 2020)
The purpose of this study was to improve the knowledge on Hura crepitans L., a plant belonging to the Euphorbiaceae family that, on the one hand, is known to be toxic, but on the other, is a source of polyphenols with health-promoting effects. Different green extraction methods were applied, varying solvent, temperature, and duration of extraction, which can influence the phytochemical profile and biological activity of plant extracts, and the extracts were fully characterized. Aqueous extracts exhibited a superior antioxidant activity, as indicated by different spectrophotometric tests, and were cytoprotective to HepG2 cells used as model cells. Liquid chromatography–mass spectrometry analyses were performed to identify the secondary metabolites involved in these effects and demonstrated that solvent, duration, and temperature indeed influenced the extraction of polyphenols. Furthermore, the most promising extract, in terms of antioxidant potential, was incorporated into liposomes with the aim of promoting cell interaction and enhancing the antioxidant activity.